2017
DOI: 10.18203/2320-1770.ijrcog20171954
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene practices among adolescent girls in a resettlement colony of Delhi: a cross-sectional study

Abstract: Background: Menarche is an important milestone in the life of a girl which signifies the onset of fertility in a woman. To understand the health consequences and importance of menstrual hygiene practices among adolescent girls, it is important to study the current practices about the same so that future interventions can be planned accordingly.Methods: This study adopted a cross-sectional study design. A total of 85 adolescent girls (10-19 years old) were interviewed by the investigator over a period of 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 11 publications
(16 reference statements)
6
33
1
Order By: Relevance
“…Previous studies found that the mean of family members in rural were 7.44 and in urban were 7.38.13. 10 The present study found that the mean age of menarche in rural participants were 12.67±0.795 years, and in urban participants were 11.82±0.892 years. Similarly, another study found that mean age of menarche was 11.9±0.9 years.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Previous studies found that the mean of family members in rural were 7.44 and in urban were 7.38.13. 10 The present study found that the mean age of menarche in rural participants were 12.67±0.795 years, and in urban participants were 11.82±0.892 years. Similarly, another study found that mean age of menarche was 11.9±0.9 years.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies found the similar results. 10,13 More than fifty percent of rural and urban girls wash their private parts with water and soap both. The Similarly previous study found that the girls washed their private parts with water and soap both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study heavy menstrual bleeding (25%) rate is higher as we performed this study in rural area and due to heavy menstrual bleeding moderate anemia is seen in 83% of adolescent females. 8,9 A similar study of Bandkhadke et al had 30.8% of adolescents had menorrhagia and anemia was the leading cause of morbidity. 10 Menstrual morbidities can be controlled by improving nutrition level of adolescent females, for this government of India had started a lot of programs like anganwadi's, mid-day meal so that adolescent girls will get better nutrition.…”
Section: Discussionmentioning
confidence: 86%
“…17 Another cross sectional study on menstrual hygiene practices among adolescent girls in a resettlement colony of Delhi including 85 adolescent girls (10-19 years old) showed that, 85.9% girls used sanitary pads during menstruation and 91.1% disposed of the absorbent by throwing along with routine waste. 18 Likewise a cross sectional study on menstrual practices among adolescent girls in rural area of Belgaum, Karnataka including 1071 adolescent girls in the age group of 10-19 years showed that, most of these adolescent girls (73.5%) used old clothes during menstruation and a large proportion of them were reusing the same during subsequent periods after washing and not properly drying. Only about 72 (26.5%) were using sanitary napkins.…”
Section: Discussionmentioning
confidence: 99%